Respuesta :

5(1-4p) + 8 = -227
 5 - 20p + 8 = -227
   -20p + 13 = -227
           -20p = -240
           /-20      /-20
                p = 12

5(1-4p) +8=-227

Simplifying 5(1 + -4p) + 8 = -227 (1 * 5 + -4p * 5) + 8 = -227 (5 + -20p) + 8 = -227

Reorder the terms: 5 + 8 + -20p = -227

Combine like terms: 5 + 8 = 13 13 + -20p = -227

Solving 13 + -20p = -227

Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -20p = -227 + -13

Combine like terms: 13 + -13 = 0 0 + -20p = -227 + -13 -20p = -227 + -13

Combine like terms: -227 + -13 = -240 -20p = -240

Divide each side by '-20'. p = 12

Simplifying p = 12